Membrane electrode assembly for polymer electrolyte fuel cells and method for manufacturing the same

The membrane electrode assembly with a self-supporting moisture management sheet and gas diffusion layer on opposite bipolar plates addresses rigidity and delamination issues, enhancing handling and power generation performance.

JP2025006150APending Publication Date: 2025-01-17JAPAN VILENE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023106777
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing membrane electrode assemblies for polymer electrolyte fuel cells face issues of poor rigidity, handling difficulties, and delamination due to the use of self-supporting moisture management sheets with small fiber diameters, leading to increased internal resistance and decreased power generation performance.

Method used

A membrane electrode assembly design with a self-supporting moisture management sheet and gas diffusion layer on opposite bipolar plates, ensuring an interlayer peel strength of 0.001N or more, and a manufacturing method involving catalyst particle dispersion to enhance bonding between layers.

Benefits of technology

The design maintains rigidity and prevents delamination, improving handling and achieving high power generation performance by ensuring strong interlayer bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006150000001
    Figure 2025006150000001
  • Figure 2025006150000002
    Figure 2025006150000002
  • Figure 2025006150000003
    Figure 2025006150000003
Patent Text Reader

Abstract

To provide a membrane electrode assembly for a polymer electrolyte fuel cell, which prevents the occurrence of interlayer delamination between a solid polymer electrolyte membrane and a gas diffusion layer.SOLUTION: A membrane electrode assembly for a polymer electrolyte fuel cell includes, from one bipolar plate to the other bipolar plate, (1) a self-supporting moisture management sheet having a conductive nonwoven fabric containing fibers having an average fiber diameter of 3 μm or less, (2) a first catalyst layer, (3) a solid polymer electrolyte membrane, (4) a second catalyst layer, (5) a moisture management layer in contact with the second catalyst layer, and (6) a gas diffusion layer, and the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer is 0.001 N or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a membrane electrode assembly for a polymer electrolyte fuel cell and a method for producing the same. [Background technology]

[0002] Conventionally, a component for a polymer electrolyte fuel cell has been one which comprises a moisture management layer (generally a porous layer having excellent water repellency that is applied to the main surface of a gas diffusion layer) on the main surface of the gas diffusion layer made of rigid carbon paper or the like, and a catalyst layer on top of that. When gas (oxygen gas or hydrogen gas) is supplied through the grooves in each of the pair of bipolar plates, the gas passes through the gas diffusion layer, the moisture management layer, and then the catalyst layer. The gas then reacts in the catalyst layer to produce water and generate electricity. The produced water passes through the moisture management layer and is discharged outside the reaction system.

[0003] The applicant of the present application has discovered that in a solid polymer fuel cell having a "gas diffusion layer-moisture management layer-catalyst layer" according to the conventional technology, the gas diffusion layer and the moisture management layer are manufactured as an integrated unit, and this results in problems with poor drainage, gas diffusion, and handling. Therefore, the problem has been solved by replacing the "gas diffusion layer-moisture management layer-catalyst layer" stacking configuration with a stacking configuration of a self-supporting moisture management sheet (hereinafter abbreviated as self-supporting moisture management sheet) having a nonwoven fabric containing conductive fibers prepared using an electrostatic spinning method, and a catalyst layer (Patent Document 1; JP 2017-195087 A). In Patent Document 1, the stacking configuration of "gas diffusion layer-moisture management layer-catalyst layer" present on both the air electrode side bipolar plate to which oxygen gas is supplied and the fuel electrode side bipolar plate to which fuel gas is supplied is replaced with a stacking configuration of "self-supporting moisture management sheet-catalyst layer." [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-195087 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the membrane electrode assembly for a polymer electrolyte fuel cell disclosed in Patent Document 1, the portion sandwiched between one bipolar plate and the other bipolar plate (in many cases, the air electrode side bipolar plate and the fuel electrode side bipolar plate), i.e., Freestanding moisture management sheet, catalyst layer, solid polymer electrolyte membrane, catalyst layer, Freestanding moisture management sheet, The lamination mode of the above does not have a gas diffusion layer made of a rigid carbon paper, etc., and therefore has a new problem of poor rigidity and poor handling properties during the manufacturing process. The reason for this is that it is known that the average fiber diameter of fibers prepared using the above-mentioned electrospinning method is 3 μm or less (e.g., JP 2020-125556 A). In other words, the average fiber diameter of the conductive fibers (carbon fibers) in carbon paper is thick (e.g., 8 μm), whereas the average fiber diameter of nonwoven fabrics containing conductive fibers produced based on conventional technology is as thin as 3 μm or less. As a result, it was thought that a self-supporting moisture management sheet equipped with a nonwoven fabric containing conductive fibers with an average fiber diameter of 3 μm or less has inferior rigidity to carbon paper.

[0006] Therefore, in order to solve the new problem described above, the applicant of the present application considered replacing only the "gas diffusion layer-moisture management layer-catalyst layer" on one bipolar plate side of a solid polymer electrolyte fuel cell with a "self-supporting moisture management sheet-catalyst layer." In other words, from one bipolar plate side to the other bipolar plate, Freestanding moisture management sheet, first catalyst layer, solid polymer electrolyte membrane, second catalyst layer, a moisture management layer in contact with the second catalyst layer; and Gas diffusion layer, A membrane electrode assembly for a polymer electrolyte fuel cell having the above-mentioned lamination pattern was investigated. A membrane electrode assembly for a polymer electrolyte fuel cell having such a stacking configuration has a gas diffusion layer made of carbon paper or the like, thereby maintaining its rigidity, and thus preventing unintended deterioration of handleability during the manufacturing process.

[0007] However, when a power generation test was carried out, a new problem occurred: delamination occurred between the solid polymer electrolyte membrane and the gas diffusion layer due to swelling and shrinkage of the solid polymer electrolyte membrane during power generation. The reason for the problem is believed to be that the "self-supporting moisture management sheet" is flexible due to the inclusion of fibers with a small average fiber diameter, and is present only on one of the bipolar plates, which makes the solid polymer electrolyte membrane more likely to swell and shrink toward the other bipolar plate. Then, the catalyst layer (the catalyst layer is often formed by coating on the main surface of the solid polymer electrolyte membrane) present on the other bipolar plate, or the catalyst layer and moisture management layer present on the other bipolar plate, move significantly toward the other bipolar plate in response to the movement of the solid polymer electrolyte membrane, resulting in delamination between the solid polymer electrolyte membrane and the gas diffusion layer (specifically, either inside the catalyst layer, between the solid polymer electrolyte membrane and the catalyst layer, inside the moisture management layer, between the catalyst layer and the moisture management layer, or between the moisture management layer and the gas diffusion layer, or in multiple locations). In particular, when a fluororesin is used as the constituent material of the moisture management layer in order to provide it with excellent water repellency, the moisture management layer is prone to peeling off from the catalyst layer, and delamination is likely to occur between the solid polymer electrolyte membrane and the gas diffusion layer. Furthermore, as long as a solid polymer fuel cell having such problems is used, an increase in the resistance within the cell and an associated decrease in generated voltage will occur, making it difficult to realize a solid polymer fuel cell with excellent power generation performance.

[0008] The present invention relates to a membrane electrode assembly for a polymer electrolyte fuel cell, which includes a membrane electrode assembly for a polymer electrolyte fuel cell that includes a "self-supporting moisture management sheet-catalyst layer" on one bipolar plate side and a "gas diffusion layer-moisture management layer-catalyst layer" on the other bipolar plate side, and aims to provide a membrane electrode assembly for a polymer electrolyte fuel cell that prevents delamination between the solid polymer electrolyte membrane and the gas diffusion layer, thereby realizing a polymer electrolyte fuel cell with excellent power generation performance. [Means for solving the problem]

[0009] The above object of the present invention can be achieved by the following invention: [1] From one bipolar plate to the other, A self-supporting moisture management sheet having a conductive nonwoven fabric containing fibers having an average fiber diameter of 3 μm or less; first catalyst layer, solid polymer electrolyte membrane, second catalyst layer, a moisture management layer in contact with the second catalyst layer; and Gas diffusion layer, A membrane electrode assembly for a polymer electrolyte fuel cell, comprising: The interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer is 0.001 N or more. Membrane electrode assembly for polymer electrolyte fuel cells. [2] From the air electrode bipolar plate to the fuel electrode bipolar plate, A self-supporting moisture management sheet having a conductive nonwoven fabric containing fibers having an average fiber diameter of 3 μm or less; An air electrode side catalyst layer, solid polymer electrolyte membrane, fuel electrode side catalyst layer, an anode-side moisture management layer in contact with the anode-side catalyst layer; and A gas diffusion layer on the fuel electrode side, A membrane electrode assembly for a polymer electrolyte fuel cell, comprising: the interlayer peel strength between the solid polymer electrolyte membrane and the fuel electrode side gas diffusion layer is 0.001 N or more; Membrane electrode assembly for polymer electrolyte fuel cells. [3] A method for producing a membrane electrode assembly for a polymer electrolyte fuel cell according to [1], comprising the steps of: (Step 1) preparing a catalyst particle dispersion in which catalyst particles are dispersed in a dispersion medium; (Step 2) applying the catalyst particle dispersion onto one main surface of the moisture management layer to form a second catalyst layer in which the catalyst particles are deposited on the one main surface of the moisture management layer; having [1] A method for producing a membrane electrode assembly for a polymer electrolyte fuel cell. [4] A method for producing a membrane electrode assembly for a polymer electrolyte fuel cell according to [2], comprising the steps of: (Step 1) preparing a catalyst particle dispersion in which catalyst particles are dispersed in a dispersion medium; (Step 2) applying the catalyst particle dispersion onto one main surface of the fuel electrode side moisture management layer to form a fuel electrode side catalyst layer in which the catalyst particles are deposited on one main surface of the fuel electrode side moisture management layer; having [2] A method for producing a membrane electrode assembly for a polymer electrolyte fuel cell. Effect of the Invention

[0010] In the manufacturing method of the present invention, a catalyst particle dispersion is applied to the main surface of a moisture management layer (a moisture management layer formed on the main surface of a gas diffusion layer) to form a catalyst layer on the main surface of the moisture management layer. This allows the components of the catalyst layer to be embedded in the moisture management layer, resulting in an interlayer peel strength of 0.001 N or more between the solid polymer electrolyte membrane and the gas diffusion layer.

[0011] The membrane / electrode assembly for polymer electrolyte fuel cells of the present invention can be realized by providing a laminate of the catalyst layer and the moisture management layer formed on the main surface of the moisture management layer. As a result, in this membrane electrode assembly for polymer electrolyte fuel cells, even if the catalyst layer formed on the main surface of the moisture management layer or the catalyst layer and the moisture management layer attempt to move significantly toward the bipolar plate side as the solid polymer electrolyte membrane swells and shrinks toward the bipolar plate side where the self-supporting moisture management sheet is present during power generation, the catalyst layer and the moisture management layer are firmly bonded together, suppressing the occurrence of delamination between the catalyst layer and the moisture management layer (particularly, even if a fluororesin is used as the constituent material of the moisture management layer so as to be highly water-repellent), and as a result, delamination between the solid polymer electrolyte membrane and the gas diffusion layer is suppressed. In particular, from the air electrode bipolar plate to the fuel electrode bipolar plate, Freestanding moisture management sheet, An air electrode side catalyst layer, solid polymer electrolyte membrane, fuel electrode side catalyst layer, Fuel electrode side moisture management layer, A gas diffusion layer on the fuel electrode side, In a membrane electrode assembly for a polymer electrolyte fuel cell having the above-mentioned stacking configuration, oxygen gas, which has a larger molecular weight than a fuel gas (e.g., hydrogen gas having a small molecular weight) and therefore has poor diffusibility, is easily diffused by the self-supporting moisture management sheet and supplied uniformly to the air electrode side catalyst layer. As a result, the rigidity is maintained, preventing unintended deterioration of handling properties during the manufacturing process, and a polymer electrolyte fuel cell with high power generation performance can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Freestanding moisture management sheet) The self-supporting moisture management sheet constituting the membrane electrode assembly for polymer electrolyte fuel cells (hereinafter, sometimes simply referred to as the membrane electrode assembly) of the present invention includes a conductive nonwoven fabric containing fibers with an average fiber diameter of 3 μm or less. The conductive nonwoven fabric is not particularly limited as long as it contains at least one type of fiber with an average fiber diameter of 3 μm or less among the constituent fibers and has conductivity as a nonwoven fabric, and can be, for example, a conductive nonwoven fabric containing conductive fibers made of organic resin containing conductive particles, a conductive nonwoven fabric in which conductive particles exist between conductive fibers made of organic resin, a conductive nonwoven fabric containing conductive fibers made of conductive components, or a conductive nonwoven fabric containing conductive fibers in which a conductive component is coated on the surface of organic resin fibers. Typically, it is a conductive nonwoven fabric containing conductive fibers made of organic resin containing conductive particles. Hereinafter, the constituent fibers of the conductive nonwoven fabric may be referred to as constituent fibers. The organic resins that can be used to form these constituent fibers may be hydrophobic organic resins or hydrophilic organic resins, and are not particularly limited. The former hydrophobic organic resins exhibit excellent water permeability and excellent drainage even without impregnating the voids of the self-supporting moisture management sheet with hydrophobic resins such as fluorine-based resins. On the other hand, hydrophilic organic resins can retain moisture, so that the solid polymer electrolyte membrane can be kept moist, and a solid polymer fuel cell that can exhibit sufficient power generation performance can be produced. Note that the organic resin does not include diamond, graphite, or amorphous carbon. This "hydrophobic organic resin" is an organic resin with a contact angle with water of 90° or more, and examples thereof include fluororesins such as polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), perfluoroalkoxy fluororesin (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and copolymers of various monomers that constitute the above resins; polyolefin resins such as polyethylene (PE) and polypropylene (PP); polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); etc. Among these, fluororesins are suitable because of their high heat resistance, chemical resistance, and hydrophobicity.

[0013] On the other hand, a "hydrophilic organic resin" is an organic resin having a contact angle with water of less than 90°, examples of which include cellulose such as rayon, polyamide resins such as nylon 6 and nylon 66, polyacrylonitrile, acrylic oxide, polyvinyl alcohol resins, acrylic resins such as polyacrylic acid and polymethacrylic acid, and resins having hydrophilic groups (amide groups, carboxyl groups, hydroxyl groups, amino groups, sulfonic acid groups, etc.) such as hydrophilic polyurethane and polyvinylpyrrolidone. The constituent fibers in the present invention may be in a mixed or composite state with one or more hydrophobic organic resins and / or one or more hydrophilic organic resins. As the conductive fiber composed of a conductive component, a fiber obtained by carbonizing the above-mentioned hydrophobic organic resin or hydrophilic organic resin fiber may be used. As such a conductive fiber, it is preferable to adopt a fiber carbonized by baking polyacrylonitrile, and it is preferable to carry out a step of infusibility (flame resistance) before the carbonization so that the fiber shape can be maintained even after the carbonization. This infusibility can be carried out, for example, by heating in an oxidizing atmosphere at a temperature of 200 to 300°C for 10 to 120 minutes. The heating can be carried out two or more times under different conditions of temperature or time. The baking conditions for carbonization can be appropriately adjusted, and can be carried out, for example, by heating in an inert gas atmosphere such as nitrogen, helium, argon, etc. at a maximum temperature of 800 to 3000°C.

[0014] The self-supporting moisture management sheet of the present invention preferably contains conductive particles so as to have excellent electron mobility. 5 The particles are less than Ω·cm and have excellent conductivity, so the 3 It is preferable that the resistance is less than 10 Ω·cm. 1 It is more preferable that the resistance is Ω·cm or less. Such conductive particles are not particularly limited, but examples thereof include carbon black, carbon nanotubes, carbon nanofibers, metal particles, and metal oxide particles. Among these, carbon black is suitable in terms of chemical resistance, conductivity, and dispersibility. The particle size of the conductive particles is not particularly limited, but the average primary particle size is preferably 5 nm to 200 nm, and more preferably 10 nm to 100 nm. The average primary particle size of the conductive particles is preferably smaller than the fiber diameter of the constituent fibers so that the conductive particles are less likely to fall off and are easily formed into a fiber form. The average particle size of the conductive particles obtained from a particle size distribution meter using a dynamic light scattering method is not particularly limited, but the average primary particle size is preferably 5 nm to 1000 nm, and more preferably 10 nm to 500 nm.

[0015] Such conductive particles may be present in any manner in the constituent fibers, but may be present inside the fibers, inside the fibers and on the outer surface of the fibers, or on the outer surface of the fibers. From the viewpoint of conductivity, it is preferable that the constituent fiber surface contains both conductive particles at least partially exposed and conductive particles buried inside the constituent fibers. In addition, it is preferable that the constituent fibers do not have a branched structure so that the variation in fiber diameter is relatively small and the surface of the self-supporting moisture management sheet has excellent smoothness. Such constituent fibers containing conductive particles can be obtained, for example, by spinning a spinning solution containing an organic resin and conductive particles using an electrostatic spinning method.

[0016] In the present invention, when the constituent fiber is a fiber containing conductive particles, the content of the conductive particles is not particularly limited, but in order to obtain excellent conductivity, the mass ratio of the conductive particles to the organic resin is preferably 10-90:90-10, more preferably 20-80:80-20, more preferably 30-40:70-30, and even more preferably 40-60:60-40. If the conductive particles are less than 10 mass%, the conductivity tends to be insufficient, and if the conductive particles are more than 90 mass%, the fiber shape retention tends to decrease.

[0017] The average fiber diameter of the constituent fibers that can constitute the self-supporting moisture management sheet of the present invention is not particularly limited as long as it is 3 μm or less, but is preferably 10 nm to 2 μm, more preferably 100 nm to 1.5 μm, and even more preferably 400 nm to 1.1 μm. If the average fiber diameter is thicker than 10 μm, there are few contact points between the constituent fibers, and the conductivity tends to be insufficient, while if it is thinner than 10 nm, it tends to be difficult to contain conductive particles inside the fibers. Note that the average fiber diameter of the constituent fibers is preferably 5 times or more the primary particle diameter of the conductive particles so that the conductive particles are less likely to fall off.

[0018] In the present invention, the "average fiber diameter" means the arithmetic mean value of fiber diameters at 40 points, and the "fiber diameter" is a value measured based on a microscopic photograph. When the conductive particles are composed only of constituent fibers exposed from the fiber surface, it means the diameter including the conductive particles exposed from the fiber surface. And, when the conductive particles do not contain constituent fibers exposed from the fiber surface, or when the conductive particles contain constituent fibers exposed from the fiber surface but the conductive particles contain constituent fibers having a part not exposed from the fiber surface, it means the diameter of the part where the conductive particles are not exposed from the fiber surface.

[0019] The constituent fibers in the present invention are preferably continuous fibers so as to have excellent electron mobility. Such continuous fibers can be produced, for example, by electrostatic spinning or spunbonding, and continuous fibers formed by electrostatic spinning are particularly suitable because they have excellent electron mobility. The term "continuous fibers" in the present invention means that when a photograph of a self-supporting moisture management sheet is taken using an electron microscope at a magnification such that one side of the photographed image is about 60 times the average fiber diameter of the conductive fibers, the number of ends of the constituent fibers per one electron microscope photograph is 0.3 or less. In other words, the number of ends of the constituent fibers per one electron microscope photograph is 0.3 or less, calculated by dividing the total number of ends of the constituent fibers in 20 electron microscope photographs by the number of photographs (20). The photographs are taken at different positions in succession in the center of the self-supporting moisture management sheet, not including the cut portion. For example, when checking whether a conductive fiber with an average fiber diameter of 1 μm is a continuous fiber, 20 photographs are taken using an electron microscope at different consecutive locations in the center of the conductive nonwoven fabric, not including the cut portion, at a magnification (2500x) such that one side of the photographed image is approximately 60 μm, and the number of ends of the constituent fibers per electron microscope photograph is calculated. If the number is 0.3 or less, the fiber can be considered to be continuous.

[0020] The self-supporting moisture management sheet of the present invention may contain the constituent fibers as described above, and may be a self-supporting moisture management sheet in which conductive particles are distributed among the constituent fibers. However, in order to make it possible to produce a fuel cell that is excellent in drainage and gas diffusion in the planar direction and has high power generation performance even under highly humidified conditions by utilizing the inherent porosity of the self-supporting moisture management sheet, the sheet may be one that is not filled with anything such as fluorine-based resin and / or conductive particles (e.g., carbon particles), etc. In other words, the sheet may be one that is composed only of constituent fibers. In particular, a self-supporting moisture management sheet may be employed in which the constituent fibers are only one type of conductive fiber.

[0021] The form of the self-supporting moisture management sheet in the present invention is not particularly limited, but it can be, for example, a nonwoven fabric, a woven fabric, or a knitted fabric. Among these, the nonwoven fabric form is preferable because it has a relatively uniform pore size and is excellent in drainage and gas diffusion properties.

[0022] When the self-supporting moisture management sheet of the present invention is in the form of a nonwoven fabric, the constituent fibers may be bonded together with an adhesive, but it is preferable that they are bonded together with an organic resin that constitutes the constituent fibers so as to have excellent electrical conductivity. Examples of suitable organic resin bonds include entanglement of the constituent fibers, plasticization bonding with a solvent, and bonding by heat fusion.

[0023] The content of conductive fibers in the self-supporting moisture management sheet of the present invention is preferably 10 mass% or more, more preferably 50 mass% or more, so as to have excellent electron mobility, and is particularly preferably composed of only conductive fibers (100 mass%). In addition, fibers other than conductive fibers may include hydrophobic organic resin fibers such as fluorine fibers and polyolefin fibers, and hydrophilic organic resin fibers such as cellulose, polyamide fibers, acrylic fibers, and polyvinyl alcohol fibers. In addition, fibers with an average diameter of more than 3 μm may be included, regardless of whether they are conductive or non-conductive.

[0024] The self-supporting moisture management sheet of the present invention may contain fibers other than conductive fibers, but in order to have excellent conductivity, the sheet should have an electrical resistance of 300 mΩ cm2 Preferably, it is less than 150 mΩ cm 2 More preferably, it is 50 mΩ cm or less. 2 The "electrical resistance" in the present invention is measured using a self-supporting moisture management sheet cut to a diameter of 25 mm (4.9 cm 2 The test piece was sandwiched between gold-plated metal plates on both sides, and a pressure of 2 MPa was applied in the lamination direction of the metal plates. The resistance value (mΩ) of the test piece was measured using a low resistance measuring device (manufactured by Hioki E.E. Corporation, model number: RM3545). Furthermore, the measured resistance value was multiplied by the area of ​​the test piece (4.9 cm2). 2 ) is the value obtained by multiplying

[0025] In order to provide the self-supporting moisture management sheet with excellent electrical conductivity, the conductive particles preferably account for 10 to 90 mass %, and more preferably 20 to 80 mass %, of the self-supporting moisture management sheet.

[0026] The basis weight of the self-supporting moisture management sheet in the present invention is not particularly limited, but is preferably 0.1 to 100 g / m from the viewpoints of ease of handling and productivity. 2 It is preferable that the thickness is 0.1 to 50 g / m 2 It is more preferable that the thickness is 1 to 500 μm, more preferably 1 to 250 μm, even more preferably 3 to 100 μm, and even more preferably 4 to 50 μm. If the thickness of the self-supporting moisture management sheet is thin, the resistance of the fuel cell can be reduced, and the volume of the fuel cell can be made smaller. This "weight" is calculated by cutting the self-supporting moisture management sheet into a 10 cm square to prepare a sample, and calculating the weight per unit area from the mass of the sample. 2 "Thickness" refers to the value converted into mass of the size of a material, and "thickness" refers to the value measured using a thickness gauge (manufactured by Mitutoyo Corporation: Code No. 547-321: measuring force 1.5 N or less).

[0027] The self-supporting moisture management sheet of the present invention utilizes its inherent porosity to provide excellent drainage and gas diffusion properties even in the planar direction, and to enable the fabrication of a fuel cell with high power generation performance even under highly humidified conditions, so that it preferably has a porosity of 40% or more, more preferably a porosity of 50% or more, more preferably a porosity of 60% or more, and even more preferably a porosity of 70% or more. This "porosity P (unit: %)" refers to the value obtained from the following formula. P = 100 - (Fr1 + Fr2 + + Frn) Here, Frn indicates the filling rate (unit: %) of component n that constitutes the self-supporting moisture management sheet, and is the value obtained from the following formula. Frn = [M × Prn / (T × SGn)] × 100 Here, M is the basis weight of the self-supporting moisture management sheet (unit: g / cm 2 ), T is the thickness of the self-supporting moisture management sheet (unit: cm), Prn is the mass ratio of component n (e.g., organic resin, conductive particles) in the self-supporting moisture management sheet, and SGn is the true density of component n (unit: g / cm 3 ) respectively.

[0028] In the self-supporting moisture management sheet of the present invention, the surface of the constituent fibers constituting the self-supporting moisture management sheet may be coated with a fluororesin so that liquid water can be easily pushed out. Examples of the fluororesin include polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), perfluoroalkoxy fluororesin (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and copolymers of various monomers constituting the above resins.

[0029] In addition, the self-supporting moisture management sheet may contain conductive particles, such as carbon particles, in the voids of the self-supporting moisture management sheet to further improve the conductivity. Even if the conductive nonwoven fabric does not contain conductive fibers, the sheet as a whole may be conductive by containing conductive particles, such as carbon particles, in the voids of the constituent fibers. Examples of the carbon particles include carbon black, carbon nanotubes, and carbon nanofibers. In addition, the sheet may be a self-supporting moisture management sheet containing conductive particles in the voids, in which carbon black particles are dispersed in a resin. Such conductive particles are not particularly limited, but can be prepared, for example, by the electrostatic spray method used in the examples.

[0030] The self-supporting moisture management sheet of the present invention can be manufactured by a conventional method. For example, the constituent fibers constituting the preferred self-supporting moisture management sheet in the form of a nonwoven fabric can be obtained by spinning using a spinning solution containing a mixture of organic resin and conductive particles, and the spun conductive fibers can be directly collected and accumulated to form a fiber web. If the fiber web is moderately entangled and has a certain degree of strength, it can be used as a self-supporting moisture management sheet, and in order to impart or improve strength, it can be bonded by plasticization with a solvent, heat fusion, adhesion with an adhesive, etc. to form a conductive porous sheet. The conductive fibers constituting the fiber web formed by directly collecting and accumulating the conductive fibers are preferably continuous fibers. This is because the continuous fibers are excellent in terms of conductivity and strength.

[0031] Examples of methods for forming the fiber web include electrostatic spinning, spunbonding, meltblowing, and a method disclosed in JP 2009-287138 A in which a gas is discharged parallel to the spinning solution discharged from a liquid discharger, and a shear force is applied to the spinning solution in a straight line to form fibers, as disclosed in JP 2009-287138 A. Among these, electrostatic spinning or the method disclosed in JP 2009-287138 A can spin conductive fibers with a small fiber diameter, making it possible to produce a thin, self-supporting moisture management sheet, which can reduce the resistance of a fuel cell and also produce a membrane electrode assembly that can reduce the volume of the fuel cell.

[0032] In addition, when using a spinning solution in which conductive particles are mixed with a solution in which an organic resin is dissolved in a solvent, as in the electrostatic spinning method or the method disclosed in JP 2009-287138 A, it is preferable to use a solvent that is not easily volatilized during spinning, and after forming a fiber web, remove the spinning solvent by solvent replacement, which makes it easy for the conductive fibers to become plasticized and bonded together, resulting in the production of a self-supporting moisture management sheet with excellent conductivity, and also because the conductive fibers adhere to each other to reduce contact resistance.

[0033] In addition, the spun conductive fibers can be wound up as continuous fibers, and then the conductive fibers can be cut to the desired fiber length to form short fibers. A fiber web can then be formed by a known dry or wet method, and the web can be bonded by plasticizing with a solvent, fusing with heat, bonding with an adhesive, or the like to form a self-supporting moisture control sheet.

[0034] Furthermore, when the surfaces of the constituent fibers are coated with a fluororesin so that the freestanding moisture management sheet can easily push out liquid water, a solution or paste containing the fluororesin is applied to the freestanding moisture management sheet by a method such as coating, spraying, or impregnation, followed by drying and firing. Similarly, when carbon is to be contained in the voids of the freestanding moisture management sheet, a solution or paste containing carbon and a fluororesin is applied to the freestanding moisture management sheet by a method such as coating, spraying, or impregnation, followed by drying and firing.

[0035] When the self-supporting moisture management sheet does not contain conductive fibers, a non-conductive nonwoven fabric can be prepared in the same manner as described above, except that a spinning solution containing an organic resin (but not containing conductive particles) is used instead of a spinning solution containing a mixture of an organic resin and conductive particles. A conductive nonwoven fabric containing conductive particles in the voids of the nonconductive nonwoven fabric can be prepared by applying a dispersion liquid containing conductive particles to the nonconductive nonwoven fabric and removing the dispersion medium by heating or the like.

[0036] (Solid polymer electrolyte membrane) The solid polymer electrolyte membrane constituting the membrane electrode assembly of the present invention may be a conventionally known one, for example, a perfluorocarbon sulfonic acid resin membrane, a sulfonated aromatic hydrocarbon resin membrane, an alkylsulfonated aromatic hydrocarbon resin membrane, an inorganic-organic composite resin membrane, etc. The solid polymer electrolyte membrane may be reinforced with a reinforcing material such as a nonwoven fabric.

[0037] (catalyst layer) The catalyst layer of the membrane electrode assembly of the present invention can be a layer containing particles having catalytic activity (hereinafter referred to as catalyst particles) and an ion exchange resin. The catalyst particles are not particularly limited, but can be, for example, platinum, platinum alloys [alloys of platinum and one or more metals selected from ruthenium, rhodium, palladium, osmium, iridium, gold, silver, chromium, iron, titanium, manganese, cobalt, nickel, molybdenum, tungsten, aluminum, silicon, zinc, and tin], or platinum or platinum alloys with catalytic activity supported on carbon such as activated carbon or carbon black. The catalyst particles can include one type, or two or more types. The catalyst particles included in the catalyst layer provided on one bipolar plate side and the catalyst particles included in the catalyst layer provided on the other bipolar plate side may be the same or different. The average particle size of the catalyst particles can be appropriately adjusted, but is preferably 1 to 20 nm. The average particle size can be measured by a transmission electron microscope.

[0038] On the other hand, the ion exchange resin can be the same as that of the solid polymer electrolyte membrane described above. That is, it can be a perfluorocarbon sulfonic acid resin, a sulfonated aromatic hydrocarbon resin, an alkylsulfonated aromatic hydrocarbon resin, an inorganic-organic composite resin, or the like. In particular, if it is the same as that of the solid polymer electrolyte membrane, it is preferable because it has excellent affinity with the solid polymer electrolyte membrane. The ion exchange resin of the first catalyst layer provided on one bipolar plate side and the ion exchange resin of the second catalyst layer provided on the other bipolar plate side may be the same or different. In addition, the ion exchange resin of each catalyst layer may be composed of one type or two or more types.

[0039] (Moisture management layer and gas diffusion layer) The gas diffusion layer used in the present invention may be any of those known in the art, such as carbon paper, carbon nonwoven fabric, or glass fiber nonwoven fabric filled with a conductive agent and a fluorine-based resin; or an organic fiber nonwoven fabric made of acid-resistant organic fibers (for example, a polyester fiber such as polytetrafluoroethylene fiber, polyvinylidene fluoride fiber, polyparaphenylene terephthalamide fiber, polyolefin fiber, polyphenylene sulfide fiber, polyethylene terephthalate fiber, or polytrimethylene terephthalate fiber, either alone or in combination). The moisture management layer used in the present invention may be a conventionally known layer such as a porous layer having excellent water repellency formed on the main surface of the gas diffusion layer described above. As an example, the moisture management layer may be a breathable layer formed on the main surface of the gas diffusion layer by applying or impregnating the gas diffusion layer with a mixture of a conductive agent such as carbon powder and a fluorine-based resin such as polytetrafluoroethylene.

[0040] (Membrane electrode assembly for polymer electrolyte fuel cells) The membrane electrode assembly of the present invention comprises the above-mentioned self-supporting moisture management sheet, solid polymer electrolyte membrane, catalyst layer, moisture management layer, and gas diffusion layer, and the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer is 0.001 N or more. In the manufacturing method of the present invention, a catalyst layer is formed on the main surface of the moisture management layer (a moisture management layer formed on the main surface of a gas diffusion layer) by applying a catalyst particle dispersion to the main surface of the moisture management layer, whereby the components of the catalyst layer are embedded in the moisture management layer, and the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer is 0.001 N or more.

[0041] (Method of manufacturing membrane electrode assembly for polymer electrolyte fuel cell) In the method for producing a membrane electrode assembly according to the present invention, as long as it includes a step of applying a catalyst particle dispersion onto one main surface of a moisture management layer to form a catalyst layer in which the catalyst particles are deposited on the main surface of the moisture management layer, the membrane electrode assembly according to the present invention can be prepared by combining various conventional methods.

[0042] As the catalyst particles used in the preparation of the catalyst particle dispersion liquid, the catalyst particles exemplified in the above-mentioned (catalyst layer) can be used. The dispersion medium used in preparing the catalyst particle dispersion liquid may be, for example, water, ethyl alcohol, propyl alcohol, butyl alcohol, or ethylene glycol dimethyl ether. The catalyst particle concentration in the catalyst particle dispersion and the coating amount of the catalyst particle dispersion can be appropriately determined so that a sufficient amount of catalyst particles is contained in the catalyst layer to be formed. The content of the catalyst particles in the catalyst layer is 0.01 to 1.0 mg / cm in terms of the catalyst amount (i.e., in the case where the catalyst particles contain a carrier, the amount excluding the carrier). 2 It can be. The catalyst layer can be formed by applying a catalyst particle dispersion onto one of the main surfaces of the moisture management layer, and then drying as desired. The method for applying the catalyst particle dispersion onto one of the main surfaces of the moisture management layer can be appropriately selected, and examples of the method that can be used include spraying, spin coating, gravure coating, bar coating, die coating, blade coating, air knife coating, roll coating, lip coating, float coating, comma roll coating, kiss coating, screen printing, and inkjet printing.

[0043] As one embodiment of the production method of the present invention, the following production method can be mentioned. In this embodiment, a self-supporting moisture management sheet (e.g., A1-1 in the examples described later) and a laminate consisting of "first catalyst layer-solid polymer electrolyte membrane-second catalyst layer-moisture management layer-gas diffusion layer" (e.g., laminate B2 in the examples described later) are separately prepared in advance, and the self-supporting moisture management sheet is laminated so as to be in contact with the main surface of the laminate on the first catalyst layer side, and the laminate is integrated by hot pressing to obtain a membrane electrode assembly.

[0044] More specifically, the self-supporting moisture management sheet can be prepared by the preparation method described above in (Self-supporting moisture management sheet).

[0045] The laminate can be prepared by separately preparing a "first catalyst layer-solid polymer electrolyte membrane" laminate and a "second catalyst layer-moisture management layer-gas diffusion layer" laminate in advance and integrating them. The "first catalyst layer-solid polymer electrolyte membrane" laminate can be prepared by preparing a catalyst layer formed on a temporary support, laminating the support on which the catalyst layer has been formed, via the catalyst layer, on one main surface of a separately prepared solid polymer electrolyte membrane, performing a hot press treatment, and then peeling off the temporary support. The "second catalyst layer-moisture management layer-gas diffusion layer" laminate can be prepared by applying a catalyst particle dispersion to the main surface of the moisture management layer side of a previously prepared "moisture management layer-gas diffusion layer" laminate to form a second catalyst layer. The two obtained laminates are stacked together such that the main surface of the solid polymer electrolyte membrane not having the first catalyst layer faces the second catalyst layer, and a hot press treatment is performed to prepare a laminate consisting of "first catalyst layer-solid polymer electrolyte membrane-second catalyst layer-moisture management layer-gas diffusion layer".

[0046] Finally, the self-supporting moisture management sheet is laminated so as to be in contact with the main surface of the laminate on the side of the first catalyst layer, and the laminate is integrated by hot pressing to obtain the membrane electrode assembly of the present invention. EXAMPLES

[0047] The present invention will be specifically described below with reference to examples, but the scope of the present invention is not limited thereto.

[0048] (Method of measuring interlayer peel strength) The interlayer peel strength in a membrane / electrode assembly for a polymer electrolyte fuel cell, which will be described later, was measured by the following procedure. (1) A rectangular piece (width 10 mm, length 50 mm) is cut out from a membrane electrode assembly for a polymer electrolyte fuel cell to prepare a test piece. (2) One side of double-sided tape is attached to the entire main surface of the gas diffusion layer (1 cm square) exposed on the test specimen, and the other side of the double-sided tape is attached and fixed to the test stand of a peel test attachment [manufactured by Imada Co., Ltd.] incorporated into a vertical motorized measuring stand. (3) The solid polymer electrolyte membrane portion of the test piece is partially peeled off with tweezers to create a gripping portion, and then fixed to a digital force gauge [model number: ZTA5N, manufactured by Imada Co., Ltd., measurement lower limit: 0.001 N] with a clip. (4) The gripped portion is pulled at a speed of 60 mm / min in a direction parallel to one of the four sides of the membrane electrode assembly for polymer electrolyte fuel cells to peel off the solid polymer electrolyte membrane. At this time, the maximum load (N) measured while the peeled length in the direction is 4 to 8 mm is measured. (5) The load is divided by the width of the test piece (1 cm) to calculate the 90° peel strength. (6) This 90° peel strength measurement is performed on five test pieces, and the arithmetic average value is calculated. This average value is regarded as the interlayer peel strength (unit: N / cm) between the solid polymer electrolyte membrane and the gas diffusion layer.

[0049] (Preparation of self-supporting moisture control sheet A1-1) A vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer was mixed as the fluororesin, carbon black particles (average particle size 280 nm) as the conductive particles, and dimethylformamide as the dispersion medium to prepare a spinning solution with a combined solids content of 12 mass% for the fluororesin and carbon black particles and a solids mass ratio of 20:80 for the fluororesin and carbon black particles. Using the prepared spinning solution, an electrostatically spun nonwoven fabric 1-1 (average fiber diameter: 0.8 μm) consisting only of conductive fibers in which carbon black particles are dispersed in a fluorine-based resin was prepared by electrostatic spinning. The electrostatically spun nonwoven fabric thus prepared was designated as a self-supporting moisture management sheet A1-1.

[0050] (Preparation of self-supporting moisture control sheet A1-2) The electrostatically spun nonwoven fabric 1-1 was subjected to a press (30° C., 2 MPa) to prepare an electrostatically spun nonwoven fabric 1-2. The electrostatically spun nonwoven fabric thus prepared was designated as a self-supporting moisture management sheet A1-2.

[0051] (Preparation of self-supporting moisture control sheet A1-3) The electrospun nonwoven fabric 1-1 was subjected to a press (150° C., 2 MPa) to prepare the electrospun nonwoven fabric 1-3. The electrospun nonwoven fabric thus prepared was designated as the self-supporting moisture management sheet A1-3.

[0052] (Preparation of self-supporting moisture management sheet A2) A vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer was mixed as the fluororesin, carbon black particles (average particle size 280 nm) as the conductive particles, and dimethylformamide as the dispersion medium to prepare a spinning solution with a combined solids content of 12 mass% for the fluororesin and carbon black particles, and a solids mass ratio of the fluororesin to the carbon black particles of 40:60. In addition, an electrostatic spray liquid was prepared by mixing vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer as a fluororesin, carbon black particles (average particle size 280 nm) as conductive particles, and dimethylformamide as a dispersion medium, with the combined solids content of the fluororesin and carbon black particles being 8 mass % and the solids content ratio of the fluororesin to the carbon black particles being set at 20:80 by mass. The prepared spinning solution was used to prepare an electrostatically spun nonwoven fabric (average fiber diameter 1.1 μm) consisting only of conductive fibers in which carbon black particles were dispersed in fluororesin. Simultaneously with the spinning, the prepared electrostatic spray solution was used to spray conductive particles (average particle diameter 4.4 μm) in which carbon black particles were dispersed in fluororesin. In this way, an electrostatically spun nonwoven fabric was prepared, in which the constituent fibers were conductive fibers and the conductive particles were distributed among the constituent fibers. The electrostatically spun nonwoven fabric thus prepared was designated as a self-supporting moisture management sheet A2.

[0053] (Preparation of self-supporting moisture control sheet A3) A spinning solution was prepared by dissolving 15 g of polyacrylonitrile in 85 g of dimethylformamide. A polyacrylonitrile nonwoven fabric (average fiber diameter: 0.4 μm) was prepared by electrostatic spinning using the prepared spinning solution. Next, the polyacrylonitrile nonwoven fabric was subjected to oxidation treatment in air at a temperature of 220 ° C for 30 minutes and at a temperature of 260 ° C for 1 hour, and further subjected to a heater adjusted to a heating temperature of 800 ° C for carbonization, thereby preparing an electrostatically spun nonwoven fabric (average fiber diameter: 0.4 μm) composed only of carbon fibers. The electrostatically spun nonwoven fabric prepared in this way was used as a self-supporting moisture management sheet A3.

[0054] (Measurement of various physical properties of a self-supporting moisture management sheet) The physical properties of the prepared self-supporting moisture management sheets A1-1 to A1-3, A2, and A3 are summarized in Table 1. The electrical resistance (unit: mΩ cm 2 ) was measured by the following method.

[0055] (Method of measuring electrical resistance) A circular sample with a diameter of 25 mm was taken from the freestanding moisture management sheet. The sample was then sandwiched between gold-plated metal plates, and a pressure of 2 MPa was applied in the lamination direction of the metal plates. In this state, the resistance value (mΩ) between the two metal plates was measured using a low resistance measuring device (manufactured by Hioki E.E. Corporation, model name: RM3545), and the measurement value was multiplied by the area of ​​the sample (4.9 cm2). 2 ) to obtain the electrical resistance (mΩ cm 2 ) was calculated.

[0056] [Table 1]

[0057] (Preparation of "First Catalyst Layer-Solid Polymer Electrolyte Membrane-Second Catalyst Layer-Moisture Management Layer-Gas Diffusion Layer" (Laminate B1) According to the Prior Art) Preparation of "first catalyst layer - solid polymer electrolyte membrane - second catalyst layer" 0.8 g of platinum-loaded carbon particles (Tanaka Kikinzoku Co., Ltd., TEC10V40E, platinum loading relative to carbon: 40% by mass) was added to 10.4 g of ethylene glycol dimethyl ether, and dispersed by ultrasonic treatment. Then, 4.0 g of a commercially available 5% by mass Nafion solution (Sigma-Aldrich, USA) was added as an electrolyte resin solution, and dispersed by ultrasonic treatment. The mixture was further stirred with a stirrer to prepare a catalyst particle dispersion. Next, this catalyst particle dispersion was applied to a support [Naflon (registered trademark), polytetrafluoroethylene tape, Nichias Co., Ltd., thickness: 0.1 mm] and dried at 60° C. with a hot air dryer, and the platinum loading on the main surface of the support was 0.4 mg / cm. 2 A catalyst layer of 1000 nm was formed. On the other hand, Nafion (registered trademark) NR211 (manufactured by DuPont, USA, melting point: 200°C or higher) was prepared as a solid polymer electrolyte membrane. On both sides of this solid polymer electrolyte membrane, a support on which a catalyst layer was formed was laminated with a catalyst layer interposed therebetween. After that, hot pressing was performed between both exposed main surfaces under conditions of a temperature of 140°C, a pressure of 2 MPa, and a time of 10 minutes, and then the support was peeled off, whereby catalyst layers (a first catalyst layer on one main surface and a second catalyst layer on the other main surface) were transferred and formed on both main surfaces of the solid polymer electrolyte membrane.

[0058] Preparation of "moisture management layer-gas diffusion layer" Carbon paper (SIGRACET (registered trademark) GDL22BB manufactured by SGL) having a microporous layer (moisture control layer) made of fluorine-based resin and carbon particles on one main surface was prepared.

[0059] Preparation of laminate B1 Finally, the microporous layer of the carbon paper with a microporous layer was placed face-to-face with one of the catalyst layers (second catalyst layer) of the solid polymer electrolyte membrane having catalyst layers on both main surfaces, and hot pressed at a temperature of 140°C, a pressure of 2 MPa, and for 10 minutes. In this way, a laminate B1 of "first catalyst layer-solid polymer electrolyte membrane-second catalyst layer-moisture management layer-gas diffusion layer" according to the conventional technology was prepared.

[0060] (Preparation of "First Catalyst Layer-Solid Polymer Electrolyte Membrane-Second Catalyst Layer-Moisture Management Layer-Gas Diffusion Layer" (Laminate B2) of the Present Invention) Preparation of "first catalyst layer - solid polymer electrolyte membrane" 0.8 g of platinum-loaded carbon particles (Tanaka Kikinzoku Co., Ltd., TEC10V40E, platinum loading relative to carbon: 40% by mass) was added to 10.4 g of ethylene glycol dimethyl ether, and dispersed by ultrasonic treatment. Then, 4.0 g of a commercially available 5% by mass Nafion solution (Sigma-Aldrich, USA) was added as an electrolyte resin solution, and dispersed by ultrasonic treatment. The mixture was further stirred with a stirrer to prepare a catalyst particle dispersion. Next, this catalyst particle dispersion was applied to a support [Naflon (registered trademark), polytetrafluoroethylene tape, Nichias Co., Ltd., thickness: 0.1 mm] and dried at 60° C. with a hot air dryer, and the platinum loading on the main surface of the support was 0.4 mg / cm. 2 A catalyst layer of 1000 nm was formed. On the other hand, Nafion (registered trademark) NR211 (manufactured by DuPont, USA, melting point: 200°C or higher) was prepared as a solid polymer electrolyte membrane. A support on which a catalyst layer was formed was laminated on one main surface of this solid polymer electrolyte membrane with a catalyst layer interposed therebetween. After that, hot pressing was performed between both exposed main surfaces under conditions of a temperature of 140°C, a pressure of 2 MPa, and a time of 10 minutes, and then the support was peeled off to transfer and form a catalyst layer (first catalyst layer) on one main surface of the solid polymer electrolyte membrane.

[0061] Preparation of "second catalyst layer-moisture management layer-gas diffusion layer" Carbon paper (SIGRACET (registered trademark) GDL22BB manufactured by SGL) having a microporous layer (moisture control layer) made of fluorine-based resin and carbon particles on one main surface was prepared. The catalyst particle dispersion was applied to the main surface of the microporous layer (moisture management layer) of the carbon paper having the microporous layer (moisture management layer). After that, it was dried at 60°C by a hot air dryer, and the platinum loading amount on the main surface of the microporous layer (moisture management layer) of the carbon paper having the microporous layer (moisture management layer) was 0.4 mg / cm. 2 A catalyst layer (second catalyst layer) was formed.

[0062] Preparation of laminate B2 Finally, the main surface of the solid polymer electrolyte membrane not having a catalyst layer was placed face-to-face with the catalyst layer of the carbon paper having a microporous layer (moisture management layer) with a catalyst layer (second catalyst layer), and hot pressed at a temperature of 140°C, a pressure of 2 MPa, and for 10 minutes. In this way, a laminate B2 of "first catalyst layer-solid polymer electrolyte membrane-second catalyst layer-moisture management layer-gas diffusion layer" according to the present invention was prepared.

[0063] (Comparative Examples 1 to 3) Each of the self-supporting moisture management sheets A1-1, A2, and A3 was laminated so as to be in contact with the main surface of the laminate B1 on the first catalyst layer side, and a hot press treatment was applied between both exposed main surfaces at a temperature of 140°C, a pressure of 2 MPa, and a time of 10 minutes to prepare a membrane electrode assembly for a polymer electrolyte fuel cell. In addition, in the membrane electrode assemblies for solid polymer fuel cells prepared in this manner, the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer was all too weak to be measured by the above-mentioned digital force gauge, and therefore the interlayer peel strength was all less than 0.001 N.

[0064] (Examples 1 to 3) Each of the membrane / electrode assemblies for polymer electrolyte fuel cells was prepared in the same manner as in Comparative Examples 1 to 3, except that the laminate B2 was used instead of the laminate B1. In the thus-prepared membrane / electrode assemblies for polymer electrolyte fuel cells, the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer was 0.05 N in all cases.

[0065] (Examples 4 to 5) Membrane / electrode assemblies for polymer electrolyte fuel cells were prepared in the same manner as in Example 1, except that the self-supporting moisture management sheets A1-2 and A1-3 were used instead of the self-supporting moisture management sheet A1-1. In the thus-prepared membrane / electrode assemblies for polymer electrolyte fuel cells, the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer was 0.05 N in all cases.

[0066] (Method of evaluating power generation performance of polymer electrolyte fuel cells) The power generation performance of the polymer electrolyte fuel cell was evaluated by the following method. A small fuel cell was prepared for public display at the FC-Cubic Technology Research Association. A membrane electrode assembly for polymer electrolyte fuel cells was sandwiched between the air electrode bipolar plate and the fuel electrode bipolar plate so that the surface pressure between the two plates was about 1 MPa, and a polymer electrolyte fuel cell was assembled. The membrane electrode assembly for polymer electrolyte fuel cells was sandwiched between the bipolar plates so that the air electrode bipolar plate and the independent moisture management sheet were in contact with each other, and the fuel electrode bipolar plate and the gas diffusion layer were in contact with each other, and the polymer electrolyte fuel cell was assembled. Then, power was generated using the solid polymer electrolyte fuel cell. The power generation of the solid polymer electrolyte fuel cell was performed under fully humidified conditions, with 500cc / min of hydrogen gas supplied to the fuel electrode side and 2000cc / min of air gas supplied to the air electrode side, the cell temperature was 80°C, and the bubbler temperature was 80°C. The potential-current curve during power generation was measured, and a current of 1.0A / cm during power generation was obtained. 2 and 2.0A / cm 2 Cell voltage (unit: V) at a current density of 1.0 A / cm during power generation 2 and 2.0A / cm 2 Cell resistance between both bipolar plates at a given current density (unit: mΩ cm 2 ) was measured.

[0067] (Method for checking delamination between solid polymer electrolyte membrane and gas diffusion layer after evaluation of power generation performance) After the power generation performance was evaluated, the membrane electrode assembly for the polymer electrolyte fuel cell was taken out from the polymer electrolyte fuel cell, and the membrane electrode assembly for the polymer electrolyte fuel cell was cut in the thickness direction and the cross section formed by the cutting was observed with an optical microscope to confirm whether or not delamination occurred between the solid polymer electrolyte membrane and the gas diffusion layer. If delamination occurred, an "X" was recorded in the table, and if delamination did not occur, an "O" was recorded in the table.

[0068] The power generation performance (1.0 A / cm during power generation) of a polymer electrolyte fuel cell using a membrane electrode assembly for a polymer electrolyte fuel cell prepared by combining the laminates A1-1 to A1-3, A2, and A3 with the laminates B1 and B2 shown in Table 2. 2 Cell voltage (unit: V) and cell resistance (unit: mΩ cm) at different current densities 2 )), and the occurrence or non-occurrence of delamination in the membrane electrode assemblies for polymer electrolyte fuel cells after the evaluation of power generation performance are summarized in Table 2.

[0069] [Table 2]

[0070] The power generation performance of a polymer electrolyte fuel cell using the membrane electrode assemblies for polymer electrolyte fuel cells prepared in Examples 1 to 5 (2.0 A / cm during power generation) 2 Cell voltage (unit: V) and cell resistance (unit: mΩ cm) at different current densities 2 )), and the occurrence or non-occurrence of delamination in the membrane electrode assemblies for polymer electrolyte fuel cells after the evaluation of power generation performance are summarized in Table 3.

[0071] [Table 3]

[0072] From the above results, it was found that the membrane electrode assembly for a polymer electrolyte fuel cell according to the present invention prevents delamination between the solid polymer electrolyte membrane and the gas diffusion layer, and can realize a polymer electrolyte fuel cell with excellent power generation performance. [Industrial Applicability]

[0073] The membrane / electrode assembly for a polymer electrolyte fuel cell of the present invention can be used for producing a polymer electrolyte fuel cell having excellent power generation performance.

Claims

1. From one bipolar plate to the other, A self-supporting moisture management sheet comprising a conductive nonwoven fabric containing fibers having an average fiber diameter of 3 μm or less; first catalyst layer, solid polymer electrolyte membrane, second catalyst layer, a moisture management layer in contact with the second catalyst layer; and Gas diffusion layer, A membrane electrode assembly for a polymer electrolyte fuel cell, comprising: the interlayer peel strength between the solid polymer electrolyte membrane and the gas diffusion layer is 0.001 N or more; Membrane electrode assembly for polymer electrolyte fuel cells.

2. From the air electrode bipolar plate to the fuel electrode bipolar plate, A self-supporting moisture management sheet comprising a conductive nonwoven fabric containing fibers having an average fiber diameter of 3 μm or less; An air electrode side catalyst layer, solid polymer electrolyte membrane, Fuel electrode side catalyst layer, an anode-side moisture management layer in contact with the anode-side catalyst layer; and A gas diffusion layer on the fuel electrode side, A membrane electrode assembly for a polymer electrolyte fuel cell, comprising: the interlayer peel strength between the solid polymer electrolyte membrane and the fuel electrode side gas diffusion layer is 0.001 N or more; Membrane electrode assembly for polymer electrolyte fuel cells.

3. A method for producing the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 1, comprising the steps of: (Step 1) preparing a catalyst particle dispersion in which catalyst particles are dispersed in a dispersion medium; (Step 2) applying the catalyst particle dispersion onto one main surface of the moisture management layer to form a second catalyst layer in which the catalyst particles are deposited on the one main surface of the moisture management layer; having A method for producing the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 1.

4. A method for producing the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 2, comprising the steps of: (Step 1) preparing a catalyst particle dispersion in which catalyst particles are dispersed in a dispersion medium; (Step 2) applying the catalyst particle dispersion onto one main surface of the anode-side moisture management layer to form an anode-side catalyst layer in which the catalyst particles are deposited on the one main surface of the anode-side moisture management layer; having A method for producing the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 2 .

Citation Information

Patent Citations

  • Membrane-electrode assembly and solid polymer fuel cell

    JP2017195087A